Returning (to) communities : theory, culture and political practice of the communal - Herbrechter, Stefan; Higgins, Michael (Critical studies (Amsterdam, Netherlands), 2006)
Returning (to) Communities offers an innovative collection of examples and case studies into what has become a hotly disputed topic. The chapters present a wide-ranging series of interventions into the new debates over the concepts and practices of "community" and the communal. For this book, scholars have been gathered from across Europe and Australia as well as from the United States, and several contributors are involved in community practice. Returning (to) Communities is essential reading to researchers and students in social policy, sociology, ethnic studies, cultural analysis, media stu.